2004
DOI: 10.1111/j.0300-9475.2004.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Low Doses of Solar‐Simulated Radiation Induces an Increase in the Myeloid Subtype of Blood Dendritic Cells

Abstract: Exposure to ultraviolet radiation causes alterations of cutaneous and systemic immunity. The aim of our study was to assess the influence of low doses of solarsimulated radiation (SSR) on the phenotypes of blood dendritic cells (BDC). Healthy volunteers (94) were irradiated with a dose of 1.2 SED (standard erythema dose) of SSR for 2, 10 or 30 consecutive days. Blood samples were taken before the first exposure and 24 h after final exposure. The three main subsets of BDC were distinguished by flow cytometry:. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
10
0
3
Order By: Relevance
“…As was previously found, these subpopulations strictly corresponded with mDC characterised by BDCA-1+/CD11c+/HLA-DR+ immunophenotype for mDC1 and BDCA-3+/CD32−/CD64−/HLA-DR+ for mDC2 subtype 23. The third subpopulation, pDC, was discriminated based on BDCA-2+/CD123+/HLA-DR+ immunophenotype (fig 1C).…”
Section: Methodssupporting
confidence: 80%
“…As was previously found, these subpopulations strictly corresponded with mDC characterised by BDCA-1+/CD11c+/HLA-DR+ immunophenotype for mDC1 and BDCA-3+/CD32−/CD64−/HLA-DR+ for mDC2 subtype 23. The third subpopulation, pDC, was discriminated based on BDCA-2+/CD123+/HLA-DR+ immunophenotype (fig 1C).…”
Section: Methodssupporting
confidence: 80%
“…Narbutt et al. (47) reported that whole‐body suberythemal SSR of volunteers daily for up to 30 days induced an increase in the percentage of DCs within the peripheral blood mononuclear population. In particular there was an increase in DCs characterized as myeloid subtype 1.…”
Section: Immune Cell Typesmentioning
confidence: 99%
“…Narbut e cols. 28 encontraram aumento de célu-las dendríticas subtipos mielóide e plasmocitóide no sangue periférico após exposição a baixas doses de radiação solar símile (SRR) que poderia refletir o elevado recrutamento de DC na pele como parte da resposta ao UVR. É bem conhecido o fato de que muitas LCs presentes na epiderme migram para os linfono- dos após a UVR, e, ao mesmo tempo, a mobilização de precursores LC, dos DDs mielóides é observada.…”
Section: Discussionunclassified
“…Haveria, assim, um provável recrutamento intenso de células dendríticas da pele, como ocorre com a exposição à radiação ultravioleta. 28,29 Sabe-se também que substâncias inibidoras dos mediadores dos mastócitos não melhoram a placa psoriásica. 27 O aumento da população de DDs FXIIIa+ após o tratamento com PTX também poderia ser explicado pela diminuição da migração dessas células da derme para os órgãos linfóides secundários.…”
Section: Discussionunclassified